Flow-cytometry reveals mitochondrial DNA accumulation in Saccharomyces cerevisiae cells during cell cycle arrest - Potapenko, Elena Yu; Kashko, Nataliia D.; Knorre, Dmitry A. (Frontiers in Cell and Developmental Biology, 2024)
Mitochondria are semi-autonomous organelles containing their own DNA (mtDNA), which is replicated independently of nuclear DNA (nDNA). While cell cycle arrest halts nDNA replication, mtDNA replication continues. In Saccharomyces cerevisiae, flow cytometry enables semi-quantitative estimation of mtDNA levels by measuring the difference in signals between cells lacking mtDNA and those containing mtDNA. In this study, we used flow cytometry to investigate mtDNA accumulation in yeast cells under G1 and G2 phase cell cycle arrest conditions utilising thermosensitive mutants cdc4-3 and cdc15-2. In line with the previous studies, cell cycle arrest induced a several-fold accumulation of mtDNA in both mutants. The total DNA levels in arrested cells correlated with cell forward scattering, suggesting a relationship between individual cell mtDNA quantity and size. In cell cycle-arrested cells, we observed no correlation between cell size and intercellular mtDNA copy number variability. This implies that as cell size increases during arrest, the mtDNA content remains within a specific limited range for each size class. This observation suggests that mtDNA quantity control mechanisms can function in cell cycle-arrested cells.